2021
DOI: 10.1029/2020jf005918
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Migrating Secondary Bedforms Can Persist on the Lee of Slowly Migrating Primary River Dunes

Abstract: Subaqueous dunes are the building blocks of sand-bedded rivers, affecting flood risk, navigation and the stability of infrastructure (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 84 publications
2
44
1
Order By: Relevance
“…Therefore, the depth-averaged flow velocity in our data set was just above incipient motion, with a measurement of 0.75 m/s during the low-flow period. Previous studies on dune migration found a dune celerity similar to the celerity found in our study during the flood waves (Ten Brinke et al, 1999) and during the low-flow period (Zomer et al, 2021).…”
Section: Reflection On Transport Stagesupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the depth-averaged flow velocity in our data set was just above incipient motion, with a measurement of 0.75 m/s during the low-flow period. Previous studies on dune migration found a dune celerity similar to the celerity found in our study during the flood waves (Ten Brinke et al, 1999) and during the low-flow period (Zomer et al, 2021).…”
Section: Reflection On Transport Stagesupporting
confidence: 91%
“…Understanding of river dune dynamics is essential for river management. Dune shape, in combination with celerity, is a proxy for sediment transport (McElroy & Mohrig, 2009; Zomer et al., 2021), which is an important quantity to calibrate morphological models. Such models can support dredging operations to enable safe navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding river geometry, the observed alternating bars in the river Waal can exert an indirect control on hydraulic roughness, which extends beyond the impact on dune properties (de Ruijsscher et al., 2020). Flow concentrates in the deepest part of the river, opposite to bars (Zomer et al., 2021). The resulting variation in flow velocity over the cross‐section is significant, which means that for a uniform bedform field the effective roughness can vary over the cross‐section.…”
Section: Discussionmentioning
confidence: 99%
“…A filter span constant c = 1/6 was chosen to filter out small features, which means that the length on which filtering takes place is 1/6 of the main bedform length. Two bedform lengths of interest were defined (Zomer et al., 2021): 5 m ± 5 (hereafter referred to as superimposed bedforms) and 100 m ± 30 (hereafter referred to as dunes), and the corresponding span values (P0) were used as input for detrending the profile (Figure 2). Bedforms smaller than 5 m could not be detected due to the grid cell size of 1 × 1 m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation